Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Pupuk Organik Cair Di Desa Waringinjaya Kecamatan Cigelis Kabupaten Pandeglang - Hayatullaela, Neng Fitri; Purwanti, Eneng; Maftuhah, Nurul; Syafitri, Viyonisa Nabilah; Sari, Windi Puspita; Himmah, Muda Fanny Darojatul (TAFANI: Jurnal Pengabdian Masyarakat, 2025)
Waringin Jaya Village, where the majority of the population relies on agriculture, faces significant challenges related to soil quality degradation and dependence on synthetic chemical fertilizers. These issues impact agricultural productivity and environmental health. As a solution, an initiative to produce liquid organic fertilizer using locally available materials is expected to transform the community's mindset and agricultural practices. Through training and mentoring, residents are encouraged to engage in the fertilizer production process, which not only enhances knowledge but also fosters a sense of ownership and responsibility toward the environment. This study aims to explore the community empowerment process in Waringin Jaya Village and analyze its impact on economic and environmental well-being. It is hoped that this research will contribute to the development of effective and sustainable community empowerment model.